2020
DOI: 10.1177/1945892420978351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Benralizumab in Patients With Severe Eosinophilic Asthma and Chronic Rhinosinusitis With Nasal Polyps: A Case Series

Abstract: Objective To analyze the effect of benralizumab in severe eosinophilic asthma (SA) and chronic rhinosinusitis with polyps (CRSwP). Methods Retrospective review of patients with both SA and CRSwP that were treated with benralizumab. Asthma controlled test (ACT), pulmonary function metrics (FEV1), Meltzer endoscopic polyp scores, SNOT-22 scores, were collected before and after at least 4 months of benralizumab therapy. Results 23 patients were included. The mean age at the time of enrollment into benralizumab th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
2
18
1
1
Order By: Relevance
“…Results from the OSTRO (benralizumab) and SYNAPSE (mepolizumab) Phase 3 trials in CRSwNP have demonstrated improvements in nasal polyp score and nasal blockage/obstruction following biologic treatment [ 29 , 30 ]. These findings are supported by studies that found a reduction in nasal polyp size, symptoms, and/or quality of life in the overlap population of patients with severe eosinophilic asthma and CRSwNP treated with benralizumab [ [31] , [32] , [33] ]. Furthermore, a randomized, double-blind, placebo-controlled study showed that mepolizumab treatment led to a reduced need for surgery in patients with severe nasal polyps receiving topical corticosteroids [ 34 ].…”
Section: Discussionsupporting
confidence: 55%
“…Results from the OSTRO (benralizumab) and SYNAPSE (mepolizumab) Phase 3 trials in CRSwNP have demonstrated improvements in nasal polyp score and nasal blockage/obstruction following biologic treatment [ 29 , 30 ]. These findings are supported by studies that found a reduction in nasal polyp size, symptoms, and/or quality of life in the overlap population of patients with severe eosinophilic asthma and CRSwNP treated with benralizumab [ [31] , [32] , [33] ]. Furthermore, a randomized, double-blind, placebo-controlled study showed that mepolizumab treatment led to a reduced need for surgery in patients with severe nasal polyps receiving topical corticosteroids [ 34 ].…”
Section: Discussionsupporting
confidence: 55%
“…Therefore, we had to accept a smaller benralizumab group with only 6 cases in this group. Although other studies showed a significant decrease in the SNOT-22 score and endoscopic polyp score, the small group size in our study made it nearly impossible to see a real trend of treatment success [15, 16]. We were also unable to include dupilumab, which also appears to be a very promising biological compound in the treatment of CRSwNP [17].…”
Section: Discussionmentioning
confidence: 81%
“…Monoclonal antibodies have been demonstrated to be very useful in the management of chronic eosinophilic diseases such as asthma and atopic dermatitis; the experience in these fields encouraged researchers to investigate efficacy of these drugs in CRSwNP. Proof-of-concept studies [35][36][37][38][39][40] were performed mainly in patients with severe asthma and nasal polyps, generating promising results and building upon successful phase 3 studies 41 . The pathophysiology of CRSwNP includes eosinophilia, T-helper cell 2 cytokines and IgE formation, and for this reason three main strategies may be undertaken with monoclonal antibodies: anti-IL-4/IL-13 signaling (dupilumab), anti-IL-5 pathways (mepolizumab, benralizumab) and anti-IgE antibodies (omalizumab).…”
Section: The New Age Of Biologics In Crs: From Scientific Evidence To Approval Of New Treatment Optionsmentioning
confidence: 99%
“…The Phase III studies, SIROCCO and CALIMA57,58 , demonstrated the efficacy and safety of benralizumab in significantly reducing annualised exacerbations rates, improving lung function and disease control vs placebo as add-on therapy to high-dosage ICS/LABA in patients with SEA and blood eosinophil counts ≥ 300 cells/ microliter. A growing body of evidence suggests that benralizumab may exert a rapid and effective therapeutic action in patients with SEA and concomitant relapsing nasal polyposis39 . Canonica et al59 presented the results of a sub-study of ANDHI phase III-b trial at EAACI congress in 2020, involving 153 patients with SEA and CRSwNP as ter 24 weeks.…”
mentioning
confidence: 99%